Metabolic bone disease in ulcerative colitis: A cross-sectional study in a tertiary care hospital of Northern India - Brij Sharma; Neetu Sharma; Vishal Bodh; Rajesh Sharma; Vineeta Sharma; Rajesh Kumar (Wolters Kluwer Medknow Publications, 2022)
Background: Metabolic bone disease (MBD), including osteomalacia, osteopenia, and osteoporosis, is common in patients with inflammatory bowel disease (IBD) and is considered to be an extraintestinal manifestation. There is a paucity of reports on MBD in patients with IBDs from India. We aimed to investigate the prevalence of MBD in adult patients with ulcerative colitis (UC). Materials and Methods: In this single-center, hospital-based, cross-sectional observational study, 161 consecutive patients of UC, between 18 and 70 years of age, were assessed for MBD with blood investigation (corrected serum calcium, phosphorus, alkaline phosphatase, serum 25-hydroxy Vitamin D3, and parathyroid hormone levels) and dual-energy X-ray absorptiometry (DEXA). Results: Out of 161 UC patients, 74 (46.0%) had Vitamin D deficiency. Osteopenia and osteoporosis of the neck of the femur on DEXA were seen in 39.7% and 11.2% of the patients, respectively. Osteopenia and osteoporosis of the lumbar spine on DEXA were seen in 33.5% and 15.5% of the patients, respectively. Conclusion: MBD is common in UC.